2013
DOI: 10.1111/tmi.12166
|View full text |Cite
|
Sign up to set email alerts
|

Migration and access to maternal healthcare: determinants of adequate antenatal care and institutional delivery among socio‐economically disadvantaged migrants in Delhi, India

Abstract: Abstractobjective To identify the determinants of adequate antenatal care (ANC) utilisation and institutional deliveries among socio-economically disadvantaged migrants living in Delhi, India.methods In a cross-sectional survey, 809 rural-urban migrant mothers with a child aged below 2 years were interviewed with a pretested questionnaire. Data on receiving antenatal, delivery and post-natal services, migration history and other social, demographic and income were collected.results Recent migrants used the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
56
1
3

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 16 publications
17
56
1
3
Order By: Relevance
“…Population movement has received much attention in the context of the HIV epidemic . Migration and mobility may be associated with HIV acquisition and providing HIV care to mobile populations presents particular challenges . In South Africa, movement between rural and urban areas for employment, education, healthcare, cultural and family reasons occurs frequently, involving all demographic groups, including women of reproductive age .…”
Section: Introductionmentioning
confidence: 99%
“…Population movement has received much attention in the context of the HIV epidemic . Migration and mobility may be associated with HIV acquisition and providing HIV care to mobile populations presents particular challenges . In South Africa, movement between rural and urban areas for employment, education, healthcare, cultural and family reasons occurs frequently, involving all demographic groups, including women of reproductive age .…”
Section: Introductionmentioning
confidence: 99%
“…11 Kusuma et al also reported that though 44.0% migrant women in Delhi availed at least one antenatal visit, the reception of various components of ANC was largely inadequate. 12 In the present study 90.3% of the women who had no ANC had no felt need. Out of the women who availed ANC, the majority (69.3%) depended on private practitioners, including unqualified practitioners.…”
Section: Discussionmentioning
confidence: 79%
“…13 In a study in Delhi, seeking ANC was reported to have a strong influence on place of delivery, 70% of women with inadequate ANC had home delivery. 12 The vaccine coverage in the 12-23 month old children was highest for the birth dose vaccines OPV-0 and BCG while it was lowest for measles. Only one-third received protection against all six VPDs though the coverage with UIP vaccines at that age should have been 100%.…”
Section: Discussionmentioning
confidence: 99%
“…One study in Malaysia found that while few migrant women never received any prenatal care during their pregnancy, they tended to initiate prenatal care as late as 7 months compared to local citizens starting prenatal care early in the first trimester [37]. Another study of migrant women in India indicated that only 37% of rural to urban migrants had adequate prenatal care and that recent migrants had prenatal visits significantly less than those who were more settled (35% VS. 39%) [38]. …”
Section: Discussionmentioning
confidence: 99%